The Strategy for Constructing the Structure: Pt-O-Ce3+ Applied in Efficient NOx Removal - Liu, Guoquan; Hao, Zhifei; Mi, Xueyue; Ma, Nan; Zhang, He; Li, Yi; Zhan, Sihui (Frontiers in Environmental Chemistry, 2021)
Exploring a unique structure with superior catalytic performance has remained a severe challenge in many important catalytic reactions. Here, we reported a phenomenon that CeO2-based catalysts loaded with different Pt precursors showed a significant difference in the performance of the reduction of NO with H2. The supported platinum nitrate [PtCe(N)] exhibited a superior low-temperature catalytic performance than the supported chloroplatinic acid [PtCe(C)]. In a wide operating temperature (125–200°C), more than 80% NOx conversion was achieved over PtCe(N) as well as excellent thermal stability. Various characterizations were used to study the microstructure and chemical electronic states. Results showed the introduction of a low valence state of Pt species into the CeO2 resulted in the rearrangement of charges on the surface of CeO2, accompanied by increasing contents of oxygen vacancies and Ce3+ sites. Furthermore, the X-ray photoelectron spectroscopy (XPS) and Raman spectra confirmed that the divalent Pt atom could substitute Ce atom to form the Pt-O-Ce3+ structure, which was the base unit in the high-performance PtCe(N) catalyst. The tunable catalytic system of the Pt-O-Ce3+ structure provides a strategy for the design of supported metal catalysts and may as a model unit for future studies of many other reactions.